Kempe mechanism in spherical space - Ming, Zhenzhen (2013)
More than a century ago, Kempe(1878) listed movable conditions for Kempe linkage (Fig.1). Fig. 1 Kempe’s linkage Kempe linkage consists of two planar fourbar linkages pivoted together (shown in yellow color). Such combinations are called double-loop planar linkages (shown in blue and red respectively), whose internal degree of freedom (DOF) is one. Objective is to find the Kempe linkage solution on the spherical surface. [Peer Assessment Review]